Monkey to man the evolution of the march of progress image - Dawson, Gowan 19XX- (Yale University Press, 2024)
"The first book to examine the iconic depiction of evolution, the 'march of progress', and its role in shaping our understanding of how humans evolved. We are all familiar with the 'march of progress', the representation of evolution that depicts a series of apelike creatures becoming progressively taller and more erect before finally reaching the upright human form. Its emphasis on linear progress has had a decisive impact on public understanding of evolution, yet the image contradicts modern scientific conceptions of evolution as complex and branching. This book is the first to examine the origins and history of this ubiquitous and hugely consequential illustration. In a story spanning more than a century, from Victorian Britain to America in the Space Age, Gowan Dawson traces the interconnected histories of the two most important versions of the image: the frontispiece to Thomas Henry Huxley's Evidence as to Man's Place in Nature (1863) and 'The Road to Homo Sapiens', a fold-out illustration in the best-selling book Early Man (1965). Dawson explores how the recurring appearances of this image pointed to shifting scientific and public perspectives on human evolution, as well as indicated novel artistic approaches and advancements in technology."--Dust jacket
Keywords: Illustration; Evolution; Mensch; Paleontological illustration; Biological illustration; Scientific illustration; Evolution (Biology) in art; Illustration biologique; Illustration scientifique; scientific illustration (process)